The Impact of International Technology Transfer on Technology Gap in the Context of Developing Countries - Mofam, Raymond Ebu; Nafiu, Akeem Tunde; Asuquo, Peter; Igwe, Anthony (Innovare Journal of Education, 2023)
The study aimed at the effect of International Technology Transfer (ITT) on the technology gap in developing countries. The study investigated the effects of ITT on the policies and strategies that can be implemented to improve ITT in developing countries. The study was anchored on dependency theory. The study employed a qualitative method. The study’s narrative review was chosen as it is an evidence-based review that concentrates on previous literature. The study used a search strategy. Previous empirical studies were screened using Prisma Flow-diagram. It was found that the effects of ITTs on the technology gap in developing countries remain a subject of debate and investigation in academic research and that empirical evidence from different studies has shown mixed findings. The study concluded that ITT could positively and negatively affect the technology gap in developing countries. The study recommended that developing countries prioritize investment in education and human capital development to build a skilled workforce capable of utilizing and adapting to new technologies. In addition, they should encourage local innovation and development of indigenous technology to reduce dependency on foreign technology and promote sustainable development.